Experimental Study of Pure Flooding Method for Localizing an Anycast Server in Wireless Ad Hoc Networks - Abed, Abdul Karim; Oz, Gurcu (IEEE, 2013)
This paper presents performance of a flooding based anycast mechanism for locating the nearest server from a group of contents-equivalent servers in real-world wireless ad hoc networks. Anycasting can be considered as an advantageous communication paradigm for ad hoc networks where resource efficiency and robustness is of the first importance. A series of experiments are conducted in an outdoor land and carried out by laptop computers running Windows Vista operating system. An application layer anycast based multithreaded program is developed and used for investigations. In experiments, the behavior of some fundamental performance metrics: response ratio, relative network traffic, average response time and duplicate ratio, was investigated with varying number of hops between source and a group of server nodes in the network.
Palestinian International Conference on Information and Communication Technology (PICICT) -- APR 15-16, 2013 -- Islam Univ Gaza, Fac Informat Technol, Gaza, ISRAEL
Keywords: wireless ad hoc networks; anycast; real-world experiment; pure flooding